#Feesmustfall and beyond: Towards a sustainable national student loan regulatory framework - Jacobs, L.; Moolman, A.M.; de Beer, E. (South African Journal of Higher Education, 2019)
Universities have been forced to raise higher education fees with above inflation rates due to increasing operating costs and higher student numbers and decreasing real term government funding. While free higher education or other alternative funding models are being considered, the higher education sector is at stake: a sector that plays a vital role in creating improved lives for all South Africans. A sustainable framework is desperately required or universities will once again need to increase student fees at unreasonable rates to maintain quality. We therefore performed a mixed method documentary analysis to prove that fee-free higher education is not viable in South Africa as significant funds will either need to be reallocated from other sectors that also require funding, or it will have to be collected from already overburdened tax payers. The present study also developed a viable student fee regulatory framework with the use of grounded theory: subsidised higher education with the effective use of the already implemented National Student Financial Aid Scheme.